Prenatal diagnosis of middle interhemispheric variant of holoprosencephaly: review of literature and prenatal case series. (12th December 2022) - Tavano, Ine; De Keersmaecker, Bart; Aertsen, Michael; De Catte, Luc
Abstract: Objective: Middle interhemispheric (MIH) variant of holoprosencephaly (HPE) or syntelencephaly is a rare prosencephalic cleavage disorder. In literature, few cases of accurate prenatal diagnosis have been reported. We report on four additional prenatally diagnosed cases. Methods: Between 2012 and 2017, four cases of MIH HPE were retrieved. Data on prenatal imaging, genetic analysis, and pathological investigation are collected. A "PubMed" and "Trip database" search were conducted revealing six papers reporting on 11 prenatally diagnosed cases. Results and discussion: Four additional cases of MIH HPE were diagnosed at an earlier gestational age (between 17 and 25 weeks of gestation) compared with 11 cases from the literature review (15–39 weeks). First trimester transvaginal ultrasound facilitates correct differentiation between the severe HPE variants. Frequent association with ZIC2 mutation was found in nearly 50% of the cases (5/11) compared with one case in our series. Conclusions: MIH variant of HPE is detectable from the early second trimester and should be considered in the differential diagnosis when the cavum septi pellucidi (CSP) is absent. Genetic analysis and autopsy should be conducted to investigate this more recent and rare variant.